Exploration of the Role of Special Mentor Teachers in Supporting the Learning of Grade 4 Students at Al Firdaus Inclusive Elementary School - Yudhani, Ardheila Setya; Fauziati, Endang; Minsih, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to identify and understand the specific role of Special Guidance Teachers (GPK) in supporting the learning process of fourth-grade students at Al Firdaus Inclusive Elementary School. Methodology: The research employs a qualitative approach using in-depth interviews and direct observation to gather comprehensive data on GPK practices and interactions. Results: The findings reveal that GPKs play a vital role in addressing the individual needs of students with special conditions by implementing personalized learning strategies, adapting subject content, maintaining active communication with parents, and collaborating with classroom teachers to develop Individual Support Plans (ISPs). These efforts contribute to notable improvements in students' academic performance, adaptive skills, and motivation. However, GPKs also face challenges such as limited resources and time constraints, which can be mitigated through innovative solutions and strong team collaboration. Applications/Originality/Value: This study highlights the strategic importance of GPKs in inclusive education settings. It emphasizes the need for continuous professional collaboration, resource allocation, and innovation to optimize inclusive practices and ensure that every child receives equitable educational support.